Independent and Interactive Effect of Plant and Mammalian Based Odors on The Response of the Malaria Vector, Anopheles Gambiae. - Jacob, Juliah W.; Tchouassi, David P.; Lagat, Zipporah O.; Mathenge, Evan M.; Mweresa, Collins K.; Torto, Baldwyn (Science Direct, 2018)
Several studies have shown that odors of plant and animal origin can be developed into lures for use in surveillance of mosquito vectors of infectious diseases. However, the effect of combining plant- and mammalian-derived odors into an improved lure for monitoring both nectar- and blood-seeking mosquito populations in traps is yet to be explored. Here we used both laboratory dual choice olfactometer and field assays to investigate responses of the malaria vector, Anopheles gambiae, to plant- and mammalian-derived compounds and a combined blend derived from these two odor sources. Using subtractive bioassays in dual choice olfactometer we show that a 3-component terpenoid plant-derived blend comprising (E)-linalool oxide, β-pinene, β-ocimene was more attractive to females of An. gambiae than (E)-linalool oxide only (previously found attractive in field trials) and addition of limonene to this blend antagonized its attractiveness. Likewise, a mammalian-derived lure comprising the aldehydes heptanal, octanal, nonanal and decanal, was more preferred than (E)-linalool oxide. Surprisingly, combining the plant-derived 3-component blend with the mammalian derived 4-component blend attracted fewer females of An. gambiae than the individual blends in laboratory assays. However, this pattern was not replicated in field trials, where we observed a dose-dependent effect on trap catches while combining both blends with significantly improved trap catches at higher doses. The observed dose-dependent attractiveness for An. gambiae has practical implication in the design of vector control strategies involving kairomones from plant- and mammalian-based
Keywords: Anopheles gambiae; Plant-based blend; Animal-based blend; Dose dependent response